Evolution of wireless communication networks: from 1G to 6G and future perspective - Ahmed Solyman, Ahmed Amin; Yahya, Khalid (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Since about 1980, a new generation has appeared approximately every decade. Mobile phones started with first-generation (1G), then the successful second generation (2G), and then mixed successful auctions since the launch of 3G. According to business terms, 1G and 2G were providing voice and gradually include data (3G is unsuccessful, 4G is very successful). Today, we are seeing a stir over what 5G will provide. Key expectations currently being discussed include an ultra-high 20 Gb/s bit rate, an ultra-low latency of just 1 millisecond, and a very high capacity. Given the enormous potential of 5G communication networks and their expected evolution, what should 6G include that is not part of 5G or its long-term evolution? 6G communication networks should deliver improved range and data speeds, as well as the ability to connect users from anywhere. This article details possible 6G communication networks. More specifically, the primary influence of this research is to deliver a complete synopsis of the development of wireless communication networks from 1G to 6G.